Self-disgust in patients with borderline personality disorder. The associations with alexithymia, emotion dysregulation, and comorbid psychopathology - Emilia Kot; Barbara Kostecka; Joanna Radoszewska; Katarzyna Kucharska (Borderline Personality Disorder and Emotion Dysregulation, 2023)
Abstract Background Self-disgust is a negative self-conscious emotion, which has been linked with borderline personality disorder (BPD). However, it has not yet been investigated in relation to both emotion dysregulation and alexithymia, which are recognized as crucial to BPD. Therefore, the aim of our study was to measure these variables and examine the possible mediational role of emotional alterations and comorbid anxiety and depression symptoms in shaping self-disgust in patients with BPD and healthy controls (HCs). Methods In total, the study included 100 inpatients with BPD and 104 HCs. Participants completed: the Self-Disgust Scale (SDS), Disgust Scale – Revised (DS-R), Toronto Alexithymia Scale (TAS-20), Emotion Dysregulation Scale short version (EDS-short), Borderline Personality Disorder Checklist (BPD Checklist), State-Trait Anxiety Inventory (STAI), and Center for Epidemiologic Studies Depression Scale (CESD-R). Results Inpatients with BPD showed higher self-disgust, alexithymia, emotion dysregulation, core and comorbid symptoms levels, and lower disgust sensitivity. Alexithymia, emotion dysregulation, and trait anxiety partially mediated between BPD diagnosis and self-disgust. The relationship between the severity of BPD symptoms and self-disgust was fully mediated by alexithymia, emotion dysregulation, depressive symptoms, and trait anxiety. Conclusions The results of our study may imply the contribution of emotion dysregulation, alexithymia, and comorbid psychopathology to self-referenced disgust in BPD.